Przegląd metod hodowli drobnoustrojów tlenowych stosowanych w procesach biosyntezy - Pietkiewicz, Jerzy Jan; Janczar-Smuga, Małgorzata (Review of the Aerobic Microorganisms Culture Methods Applied in Biosynthesis Processes, 2008)
The paper presents classification of the aerobic microorganisms culture methods. The culture method is a primary parameter of a bioprocess' efficiency. To the main criteria of this classification belong physical state of culture medium, biomass dispersion or immobilization, method of substrate feed, volume of culture medium in bioreactor, and culture techniques. Microorganisms culture methods applied in biomass' biosynthesis or in production of bioproducts are characterized in this paper as well. The ordered knowledge of bioprocess' method enables a suitable choice of biotechnology and assures optimal use of the microorganisms. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 104-123